Digital dissemination of information about mosque activities to communities - Asri N.A.; Mohamed M.A.; Mamat A.R.; Mohamad Z.; Amin M.A.M.; Nor M.A.M.; Jamil N. (Science Publishing Corporation Inc, 2023)
Android conveniently provides a platform for a variety of usage as an information highway application. Currently there is a lacking in tools and technology that is responsible for enliven the mosque especially for disseminating information related to activities and events to the community. Existing application allow communities to access via smart phone information about prayer times, Qiblat direction and tracking of the nearest mosque to perform prayer. However, there is no available application which can help to manage mosque, in par-ticular that is capable of providing solution at the entirety with capability to inform the communities, monitor and control activities and finally reporting on all matters. Our proposed Android Based Mosque Management Application is developed for this tasks. On top of that, this application implements one-time password algorithm as security element. This application is expected to serve as a platform in bringing the community into strengthening their Jemaah and helps people to stay connected with their mosque and hence contribute to enliven the mosques. 2018 Authors.